2011
DOI: 10.1093/jac/dkr240
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence and dissemination of NDM-1 metallo- -lactamase in India: data from the SMART study (2009)

Abstract: A range of carbapenemase genes, associated with diverse ESBLs and/or AmpC backgrounds, were found among Enterobacteriaceae isolated during the study. Many of these ertapenem non-susceptible strains were clonally related and carried various combinations of β-lactamases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 25 publications
7
120
0
1
Order By: Relevance
“…However, carbapenems are now frontline antibiotics in many more clinical situations than before because of the emergence and spread of ESBL-and plasmid-mediated AmpCproducing Enterobacteriaceae. The emergence of transferable resistance to these antibiotics, which are now disseminating very rapidly, is a public health emergency because of the very limited commercially available antimicrobials showing activity against carbapenemase-producing Gram-negative bacteria [Tortola et al 2005;Hirsch and Tam 2010;Carrer et al 2010;Lascols et al 2011;Nordmann et al 2011;Patel and Bonomo 2011;Glupczynski et al 2012]. This is due to the hydrolytic activity of these enzymes against b-lactams, but also to the fact that these organisms usually harbour resistance mechanisms affecting other classes of antibiotics (e.g.…”
Section: Other Drugsmentioning
confidence: 99%
“…However, carbapenems are now frontline antibiotics in many more clinical situations than before because of the emergence and spread of ESBL-and plasmid-mediated AmpCproducing Enterobacteriaceae. The emergence of transferable resistance to these antibiotics, which are now disseminating very rapidly, is a public health emergency because of the very limited commercially available antimicrobials showing activity against carbapenemase-producing Gram-negative bacteria [Tortola et al 2005;Hirsch and Tam 2010;Carrer et al 2010;Lascols et al 2011;Nordmann et al 2011;Patel and Bonomo 2011;Glupczynski et al 2012]. This is due to the hydrolytic activity of these enzymes against b-lactams, but also to the fact that these organisms usually harbour resistance mechanisms affecting other classes of antibiotics (e.g.…”
Section: Other Drugsmentioning
confidence: 99%
“…However, as carbapenemases began to emerge worldwide, the effectiveness of this last-line antibiotic class was challenged. 4 There is insufficient data regarding expression of ESBL, AmpC and metallo-β-lactamases (MBL) by E. coli strains causing extraintestinal infections in India. Hence, the present study was undertaken to find out the prevalence of ESBL, AmpC and MBL production among ExPEC isolates in a tertiary care hospital and to co-relate such infections with treatment and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A worldwide study carried out in two hundred and thirty five isolates of Enterobacteriaceae from intraabdominal infection selected on the basis of their reduced susceptibility to ertapanam (breakpoints MICs ≥ 0.5 mg/L) showed that a large proportion of isolates originated from India (68%). Also of this all the thirty-three bla NDM-1-carrying isolates were from patients in India and comprised five different species [12]. A study carried out in India in 464 isolates, 57 (12.3%) showed a reduced susceptibility to imipenem and meropenem and further showed that all the carbapenamaseresistant isolates were bla (NDM-1) positive by PCR and 13 isolates bore variants that differed in sequence from bla (NDM-1) which were NDM-5, NDM-6, and NDM-7 [13].…”
Section: National Statusmentioning
confidence: 99%